Vocabulary learning strategies of English for business students / Nalini Manoharan - Nalini , Manoharan (2019)
The research focuses on English vocabulary learning strategies used by the first and second semester of the academic year 2017 business students from one of the well known private colleges in Subang Jaya. The main aims of this study are to identify a) the most and least preferred vocabulary learning strategies used by business students and compare the vocabulary items used by low, average and high proficiency business students; b) contributing factors for business students in choosing particular vocabulary learning strategies. As this is a mixed method study, multiple sources of data were collected via semi-structured interviews with five pupils and a 25-items questionnaire based on Schmitt’s Taxonomy (1997) which was adopted from Natpassorn Rian Kamal (2008) administered to sixty eight business students. The data collected from the questionnaire was analyzed on percentages, frequencies, and means. The interview data were obtained and summarized. The finding of the study revealed that the most preferred vocabulary learning strategies were metacognitive strategies and the least preferred vocabulary learning strategies were social (consolidation) strategies by business students. Business students used vocabulary items to learn new words based on their level of proficiency. The finding based on the interview revealed many contributing factors for business students to use vocabulary learning strategies such as; a) improve other study skills; b) help and guide to remember new words; c) practical and convenient to use; d) build confidence e) make learning English more fun; and f) improve both English language and mother tongue.